STUDENTS VISUAL EXPRESSION TOWARD ONLINE LEARNING WHILE COVID-19 PANDEMIC - Saputra, Muhammad Ari (ENGLISH JOURNAL, 2022)
This study describes students’ visual expression of online learning during Covid-19 pandemic. The aim of this study was to describe facial expression of the students during online learning by following Ekman (2003) theory of face: surprise, fear, anger, disgust, sadness, and happiness. The teacher must understand if students understand what he has been saying. There were interest, concentration, and perplexity produced by face (Ekman, 2003:3). This research is beneficial for teachers or lecturer to understand the facial expressions produced by students during the teaching process, to understand how students feel in the classroom. The descriptive method was used in this study, along with a qualitative approach. The focus of this study was on students’ visual expression while online learning. There are 10 data of facial expression were identified in online learning. The data showed 20% of those with surprise expression, 10% of those with fear expression, 10% of those with disgust expression, 10% of those with anger expression, 30% of those with happiness expression and 10% with sadness expression. The data are presented in visual expression while online learning produced by the students. The findings of this study illustrate that online learning is not very effective in distance learning, which can be seen in the facial expressions of students during the teaching process